TOPICAL DRUG DELIVERY OF GOSSYPIN FROM PRONIOSOMAL GEL FORMULATIONS: IN VITRO EFFICACY AGAINST HUMAN MELANOMA CELLS - RAJKUMAR, JAMPALA; RADHA, G.V.; GANAPATY, S. (International Journal of Applied Pharmaceutics, 2021)
Objective: This work aimed to establish and formulate the gossypinproniosomal gel drug delivery system. Methods: Gossypin-loaded proniosomal gels (GPG) was prepared using specific non-ionic surfactants (Spans), followed by particle size (PS), entrapment efficiency (percent EE), in vitro, ex-vivo drug release, and in vitro efficacy of Gossypin against human melanoma cells (A-375). Results: The results showed that the percentage EE for the GPG is appropriate (81.3 %–95.5 %) and they are Nano-sized (189.3–912.0 nm) and the gels diffusion provided the desired sustaining effect for GPG-F7 formulation (75.5 percent). The GPG reported cell viability of 14.9±2.3 percent compared with 16.1±1.1 percent for free Gossypin at the maximum dose of 100 μg/ml for A-375 human melanoma cells after 24 hr incubation time. No major changes were seen in the percentage EE, PS of GPG after storage for 90d, in the physical stability report. Conclusion: The results obtained suggest that the proniosomal drug delivery system can enhance the flux to the skin and achieve the ideal Gossypin sustainability effect. Consequently, the use of proniosomal gel may be advantageous with regard to the topical delivery of Gossypin for melanoma treatment management.